Ribosomal control in RNA virus-infected cells - Wang, Xiao; Zhu, Jie; Zhang, Da; Liu, Guangqing (Frontiers in Microbiology, 2022)
Viruses are strictly intracellular parasites requiring host cellular functions to complete their reproduction cycle involving virus infection of host cell, viral genome replication, viral protein translation, and virion release. Ribosomes are protein synthesis factories in cells, and viruses need to manipulate ribosomes to complete their protein synthesis. Viruses use translation initiation factors through their own RNA structures or cap structures, thereby inducing ribosomes to synthesize viral proteins. Viruses also affect ribosome production and the assembly of mature ribosomes, and regulate the recognition of mRNA by ribosomes, thereby promoting viral protein synthesis and inhibiting the synthesis of host antiviral immune proteins. Here, we review the remarkable mechanisms used by RNA viruses to regulate ribosomes, in particular, the mechanisms by which RNA viruses induce the formation of specific heterogeneous ribosomes required for viral protein translation. This review provides valuable insights into the control of viral infection and diseases from the perspective of viral protein synthesis.